Regional Anesthesia and Ultrasound-Guided Peripheral Nerve Blocks in Current Practice - Tjokorda Gde Agung Senapathi (Jurnal Anestesiologi dan Terapi Intensif, 2026)
This editorial underscores the increasing centrality of regional anesthesia in contemporary anesthesiology, as reflected in the current issue. Peripheral nerve blocks and ultrasound-guided techniques are highlighted as key drivers of a broader shift toward precision, safety, and patient-centered perioperative care. Regional anesthesia has evolved beyond its traditional role, contributing to improved postoperative outcomes through optimized analgesia, reduced opioid use, and enhanced recovery. The integration of ultrasound has further strengthened accuracy, reproducibility, and educational value in clinical practice. However, the expansion of these techniques must be supported by adequate training, standardization, and vigilant attention to patient safety. Overall, this issue illustrates an evolving discipline in which innovation must remain aligned with evidence-based practice and clinically meaningful outcomes.